Sport event leveraging aimed at destination brand benefits: The case Cameroon - Tembi M. TICHAAWA; Janice D. HEMMONSBEY (Editura Universităţii din Oradea, 2023)
The study sets out to determine event attendee perceptions on sport event leveraging which is aimed at destination brand benefits for Cameroon. The study employed a quantitative inquiry whereby data were collected from sport event attendees at various stadiums in Cameroon during the 2021 African Cup of Nations. The findings reveal that there are clear means for event leveraging for Cameroon which primarily link to economic development and is reflected in the lengthening of visitor stays. Further, the results expose the clear brand messages of Cameroon through event hosting, which are effectively felt in promotional activities but are not affected in practice by key event brand stakeholders and the government. This shows that leveraging, especially through event media is haphazardly implemented, which therefore presents critical implications for practice. Beyond the contribution to the extant event leveraging knowledge which is reflected in the extension of the scope in event leveraging theories, this research contributes to event stakeholders involved in leveraging regarding policy development and decision-makers in strategic planning for event hosting.